Study on the Role of Cell Signaling Molecules in the Pathogenesis of Glomerulonephritis in Children - Angela Ciuntu (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Background: Cytokines are a functional class of tiny proteins and glycoproteins that are primarily monomers that act as soluble mediators in an autocrine or paracrine manner. Cytokines are produced by a variety of cell types, the majority of which are leukocytes, and their targets include both immune and non-immune cells. The study aimed to evaluate the urinary concentration of cellular signaling molecules in children with glomerulonephritis with different clinical-evolutionary stages of the disease. Materials and Methods: This study included 75 children with glomerulonephritis (GN) ranging in age from 2 to 17. 20 children had steroid-sensitive nephrotic syndrome (SSNS), 15 had steroid-resistant nephrotic syndrome (SRNS), 20 had chronic glomerulonephritis (GN) nephrotic form, and 20 had chronic GN mixed type. Patients with illness relapse and clinical remission were the subjects of this investigation. There were 20 healthy children in the control group. Results: The findings of this study revealed increased levels of cell signalling molecules (IL-8, TNF-\(α\), MCP-1, MIP-1\(α\)) in the urine during clinical manifestations, which is a significant finding given their importance in the immunopathogenic mechanism of proteinuria in nephrotic syndrome (NS). Conclusions: Determining urinary concentrations of cellular signalling molecules may be useful as a non-invasive predictive method for estimating disease activity, monitoring disease progression, distinguishing steroid-sensitive nephrotic syndrome from steroid-resistant nephrotic syndrome, and assessing treatment effectiveness in children with glomerulonephritis.